2013
DOI: 10.21831/pep.v15i1.1090
|View full text |Cite
|
Sign up to set email alerts
|

Studi Simulasi Menggunakan Fuzzy C-Means Dalam Mengklasifikasi Konstruk Tes

Abstract: Tulisan ini memperkenalkan metode fuzzy c-means dalam mengklasifikasi konstruk tes. Untuk memverifikasi sifat unidimensional suatu tes biasanya menggunakan analisis faktor sebagai bagian dari statistik parametrik dengan beberapa persyaratan yang ketat sedangkan metode fuzzy c-means termasuk metode heuristik yang tidak memerlukan persyaratan yang ketat. Studi simulasi penelitian ini menggunakan dua metode yakni analisis faktor menggunakan program SPSS dan fuzzy c-means menggunakan program Matlab. Data simulasi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The use of simulation methods provides a descriptive and dynamic grouping description of all planned designs. (Rukli, 2011). For this reason, researchers recommend simulation methods should be carried out in an educational environment to improve the learning achievement of prospective teachers.…”
Section: Professional Competencementioning
confidence: 99%
“…The use of simulation methods provides a descriptive and dynamic grouping description of all planned designs. (Rukli, 2011). For this reason, researchers recommend simulation methods should be carried out in an educational environment to improve the learning achievement of prospective teachers.…”
Section: Professional Competencementioning
confidence: 99%
“…Previous studies have shown that the determination of DLTI has never been considered, carried out, or used by teachers to present test items to students because teachers have limitations, especially in assessment and computer skills. On the other hand, DLTI is always discussed and complained about by many parties, including students and even parents, when receiving report cards or homeroom meetings when their grades are not good (Rukli, 2011). If this fact continues, it can reduce students' perceptions of mathematics so that motivation and interest in learning are less functional in educating the nation's children.…”
Section: Introductionmentioning
confidence: 99%